Influence of Macro and Internal Factors of Bank on Non Performing Loan (NPL) Bank in Indonesia Year 2011-2015 - Ardian Prima Putra, Suryo Ediyono, Nunun Tri Widarwati Sri Wahyu Agustiningsih & Purwanto (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
-